×

Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
Prove that: Tanx tan(x+60)+tanx tan(x-60)+tan(x+60) tan(x-60)=-3
Prove that: Tanx tan(x+60)+tanx tan(x-60)+tan(x+60) tan(x-60)=-3

```
3 years ago

Shailendra Kumar Sharma
188 Points
```							Tan(A-B) =TanA-TanB/(1+TanATanB) => TanATanB+1=(TanA-TanB)/Tan(A-B)SoTanxTan(60+x)+1 ={Tan(60+x)-Tan60}/Tan60 -----1Tanxtan(x-60)+1= {Tanx- Tan(60-x)}/tan60---------2Tan(x+60)tan(x-60)+1  ={tan(60+x)-tan(x-60)}/tan120--------3Adding 1,2 and 3we get TanxTan(60+x)+1+Tanxtan(x-60)+1+Tan(x+60)tan(x-60)+1=0soTanx tan(x+60)+tanx tan(x-60)+tan(x+60) tan(x-60)=-3
```
3 years ago
Think You Can Provide A Better Answer ?

Other Related Questions on Trigonometry

View all Questions »

Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution

Course Features

• 31 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions